CRIMINAL BEHAVIOR: EVALUATION OF LABELING AND CONFLICT PERSPECTIVES - Karimu, Olusola O. (European Scientific Journal, ESJ, 2015)
This article takes a comprehensive look at the utilities of criminological theories by analyzing and evaluating the general arguments and assumptions of labeling and conflict theories, and noted that both perspectives are part of the radical and critical theoretical orientations in criminology. The current paper was able to justify the testability, applicability and usefulness of both theories and notes that they are responsible for some wide ranging policies and evidence based programs geared towards addressing and controlling delinquent and criminal behavior in the society. It is also the argument of this paper that theories of criminal behavior are useful in the sense that most policies response to criminality emanates from one form or combination of theoretical perspectives.